Perbandingan Antara Muscle Energy Technique Dengan Static Stretching Terhadap Nyeri Myofascial Pain Syndrome Musculus Upper Trapezius Pada Pekerja Batik Tulis Di Industri Batik Danar Hadi Surakarta - Putra, I Kadek Indra Sentana, Totok Budi Santoso, S.Fis., S.Pd., M.PH (2017)
Background: In the process of making batik, neck muscles of batik tulis's worker was work in undergo static to preserve the head position in forward head posture. One of the problem that appear is myofascial pain syndrome musculus (m.) upper trapezius. Purpose:To determine the effect and difference of muscle energy technique (MET) and static stretching on pain in myofascial pain syndrome m. upper trapezius. Method: This study used a quasi-experimental method with two group pre test and post test design. Samples were taken by purposive sampling technique as much as 32 respondents. Data tested by paired sample t-test and independent sample t-test. Result: This study used a measuring instrument of pain visual analog scale (VAS). Based on paired sample t-test. The results in group I (MET) values of significance (p) = 0.000 (p <0.05) and group II (static stretching) value of p = 0.000 (p <0.05) means MET treatment and static stretching effect on myofascial pain syndrome m. upper trapezius. In independent sample t-test showed the value of p = 0.015 (p <0.05), which means there are differences in group I and group II. Conclusion: There is influence of MET to reduce pain on myofascial pain syndrome m. upper trapezius, there is influence of static stretching to reduce pain on myofascial pain syndrome m. upper trapezius and there is difference effects of MET and static stretching to reduce painon myofascial pain syndrome m. upper trapezius. MET better in reducing myofascial pain syndrome m. upper trapezius than static stretching. Keyword:Muscle Energy Technique, Static Stretching, Myofascial Pain Syndrome Musculus Upper Trapezius